Capitalism Reconnected Toward a Sustainable, Inclusive and Innovative Market Economy in Europe - Balkenende, Jan Peter (Amsterdam University Press, 2024)
Capitalism has gone astray. Today we face ecological exhaustion, persistent inequality, financialization, stress on communities, short-termism, and new power concentrations. An avalanche of new economic thinking and a reorientation of European values show the way toward a different economy. A new perspective is necessary if we want to implement the Sustainable Development Goals and if we consider our planet as 'Our Common Home,' for present and future generations. This book argues that European economies should be the initiators of a global transition toward a sustainable and inclusive world economy. Together, amid severe geopolitical and geoeconomic challenges, they need to develop their own perspective on what a good economy really is, in distinction to Chinese state capitalism and American big business capitalism. Crucially, this requires the rediscovery of key European values, a coherent view on responsible capitalism, and a new self-awareness as a global player for the Common Good in today's and tomorrow's world.